Physical therapy interventions for the correction of equinus foot deformity in post-stroke patients with triceps spasticity: A scoping review - Campanini, Isabella; Bò, Maria Chiara; Salsi, Francesca; Bassi, Maria Chiara; Damiano, Benedetta; Scaltriti, Sara; Lusuardi, Mirco; Merlo, Andrea (Frontiers in Neurology, 2022)
Objective Equinus foot deformity (EFD) is the most common deformity following a stroke. Several approaches have been suggested for its correction, including pharmacological, surgical, and physical therapy (PT) interventions. This scoping review aims to map and synthesize the available evidence focusing on physical therapy treatments for EFD caused by triceps surae (TS) spasticity. Methods Scoping review methodological frameworks have been used. Pubmed, Cinahl, and Cochrane databases were searched for primary literature. Studies focusing on the treatment of EFD in adult stroke patients were included only when the intervention involved PT treatments and presented at least one outcome measure for the functional and/or structural condition of the TS. Data were systematically collected and reported in tables inclusive of type of intervention, sample characteristics, dosage, comparators, outcomes, follow-up timeline, and treatment efficacy. A narrative synthesis was also added. Results Of the 642 experimental or observational screened studies, 53 were included, focusing on stretching exercises, shock waves, electrical stimulation, dry needling, TENS, vibration therapy, ultrasounds, cryotherapy, and active physiotherapy. Patients with EFD benefited from specific physical therapy treatments. These usually resulted in Modified Ashworth Scale reduction, typically by 1 point, and an increase in ROM. Interventions consisting of shock waves, dry needling, and electrostimulation showed the best results in reducing EFD. Heterogeneous dosage and delivery mode generally limited conclusions. Conclusions This scoping review summarized available primary literature based on PT treatments for the correction of EFD. By highlighting the remaining gaps in knowledge, it provides a reference for future studies on this pathology. Further investigations are necessary to pinpoint the best dosage and delivery methods. Future studies should investigate whether early rehabilitation programs started during the acute phase might help prevent or limit the development of secondary deformities.